ANALYSIS OF ZAKAT DISTRIBUTION IN ISLAMIC PERSPECTIVE - harahap, siti khodijah (Universitas Muhammadiyah Sumatera Utara, 2024)
Zakat in Islam is an obligation that must be carried out by every Muslim because it functions as a tool given by Islam to remove poverty from society by telling the rich about what they can do and their social responsibilities. There are two types of zakat distribution in Indonesia, consumptive and productive distribution. The purpose of this research is to find out about risk management in Islamic business. This article is a qualitative descriptive study, which explains the distribution of zakat from an Islamic perspective. The results of this paper show that the distribution of zakat from an Islamic perspective has the conditions and pillars of zakat, the benefits of zakat, the mechanism for distributing zakat, the groups of zakat recipients, and the legal basis for zakat, both from law and the arguments of the Qur'an and hadith